Clinical manifestation of HIV/AIDS patients: differences between public and private hospitals in Jakarta (Faculty of Medicine Universitas Indonesia, 2004)
The aims of this study is to determine the demographic data, risk factors, clinical presentations, opportunistic/co-infections and its difference between public and private hospitals. A retrospective -descriptive study was conducted in Dr. Cipto Mangunkusumo National General Hospital (public hospital) and Medistra Hospital (private hospital), Jakarta. The inclusion criteria were new HIV/AIDS cases admitted in year 2002-2003 and positive HIV serology (Elisa method). Secondary data were collected form medical record. Sixty-six subjects were enrolled in this study (public hospital 30 subjects and private hospital 36 subjects), consist of 59 male (89.4%) and 7 female (10.6%). Thirty-seven percent subjects were defined as HIV and 62% AIDS. Risk factors obtained include drug user (59.1%), homosexual (13.6%), heterosexual (21.1%), transfusion (1.5%) and maternal-child (perinatal) (1.5%). The clinical symptoms mainly present as acute fever (56.2%), weight loss (39.4%), cough (38.8%), shortness of breath (27.2%), chronic diarrhea (22.8%), prolong fever (19.7%), loss of conciousness (15.3%), anorexia (15.3%). Significant differences between public and private hospitals were seen in fever and cough symptoms. Clinical presentation of HIV/AIDS patients during admission were : pneumonia (56%), oral trush (22.6%), anemia (56.5%), leucopenia (32.3%), lymphopenia (55.9%), elevated AST/ALT (66.1%), hypoalbuminemia (46.9%), limphadenopathy (10.6%), brain space occuping lesion (7.6%), encephalopathy (6.0%), pulmonary tb and pleural effusion (10.6%). The opportunistic and co-infections present were candidiasis (25.8%), chronic hepatitis C (24.2%), chronic hepatitis B and C (4.5%), pulmonary tb, lymphadenitis and miliary tb. Candidiasis and pulmonary tb were frequently found in public hospital. In conclusion from this study that clinical manifestation of HIV/AIDS were young man or woman, with one or more possible risk factor, had fever, respiratory complain, loss of body weight, chronic diarrhea, fatique, oral trush, anemia, leucopenia, lymphopenia. Patients admitted in private hospital had varied complain; and patients that admitted in public hospital had more severe and advance condition. (Med J Indones 2004; 13: 232-6)